On DM- Compact Smarandache Topological Semigroups - Gaze Salih Al-Khafajy, Dheia; Abdulridha Mutar, Mohammed (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this present paper, we have introduced some new definitions On DM-compact Smarandache topological semigroup and DM-L. compact Smarandache topological semigroup for the compactness in topological spaces and groups. We obtained some results related to DM-compact Smarandache topological semigroup and DM-L. compact Smarandache topological semigroup, for example any infinite group can be a DM- compact Smarandache topological semigroup.